Pelatihan dan Pendampingan Manajeman Keuangan Bagi Pelaku UMKM Desa Nagasepaha Kecamatan Buleleng - Gede Widiadnyana Pasek; Ni Made Sri Ayuni; Ni Wayan Novi Budiasni (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
An understanding of financial management can monitor or see the extent to which a business is generating profits, business performance, controlling the flow of business funds, but there are still many small business actors in Nagasepaha Village who feel they do not need information in financial management because it is considered difficult and all the limitations it has. This has an impact on the continuity of business actors in Nagasepaha Village. This service is carried out through the Satya Dharma School of Economics Research and Community Service Center in collaboration with the Nagsepaha Village Head Office. In this Community Service activity, small business actors are given financial management material, namely about insight into the importance of financial management to manage a business. Implementation of activities using the lecture, discussion and question and answer method by starting with the provision of material on management of profits in small businesses that can be understood by small business actors. The results of this community service activity can help small business actors increase their knowledge and understanding of financial management